Bioremediation of tetracycline antibiotics-contaminated soil by bioaugmentation. Issue 55 (7th September 2020) - Hong, Xiaxiao; Zhao, Yuechun; Zhuang, Rudong; Liu, Jiaying; Guo, Guantian; Chen, Jinman; Yao, Yingming
Abstract : Bioaugmentation using specific microbial strains or consortia was deemed to be a useful bioremediation technology for increasing bioremediation efficiency. Abstract : Bioaugmentation using specific microbial strains or consortia was deemed to be a useful bioremediation technology for increasing bioremediation efficiency. The present study confirmed the effectiveness and feasibility of bioaugmentation capability of the bacterium BC immobilized on sugarcane bagasse (SCB) for degradation of tetracycline antibiotics (TCAs) in soil. It was found that an inoculation dose of 15% (v/w), 28–43 °C, slightly acidic pH (4.5–6.5), and the addition of oxytetracycline (OTC, from 80 mg kg −1 to 160 mg kg −1 ) favored the bioaugmentation capability of the bacterium BC, indicating its strong tolerance to high temperature, pH, and high substrate concentrations. Moreover, SCB-immobilized bacterium BC system exhibited strong tolerance to heavy metal ions, such as Pb 2+ and Cd 2+, and could fit into the simulated soil environment very well. In addition, the bioaugmentation and metabolism of the co-culture with various microbes was a complicated process, and was closely related to various species of bacteria. Finally, in the dual-substrate co-biodegradation system, the presence of TC at low concentrations contributed to substantial biomass growth but simultaneously led to a decline in OTC biodegradation efficiency by the SCB-immobilized bacterium BC. As the total antibiotic concentration was increased, the OTC degradation efficiency decreased gradually, while the TC degradation efficiency still exhibited a slow rise tendency. Moreover, the TC was preferentially consumed and degraded by continuous introduction of OTC into the system during the bioremediation treatment. Therefore, we propose that the SCB-immobilized bacterium BC exhibits great potential in the bioremediation of TCAs-contaminated environments.